Interleukin-6 predicts recovery of systolic function after myocardial infarction. (11th May 2022) - Jenca, D; Jarolim, P; Melenovsky, V; Mrazkova, J; Sramko, M; Zelizko, M; Kotrc, M; Franekova, J; Viczenova, D; Adamkova, V; Kautzner, J; Wohlfahrt, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Health of the Czech Republic Background: Interleukin (IL)-6 is an important mediator of the inflammatory response to acute myocardial infarction (MI). Increased IL-6 levels are associated with adverse outcomes after MI. However, there are only limited data on the association of IL-6 levels with recovery of systolic function after MI. Purpose: The aim of the present study was to evaluate the independent predictive value of IL-6 level for recovery of systolic function among patients hospitalized for their first MI. Methods: Consecutive patients without previous history of MI or cardiomyopathy with left ventricular ejection fraction (LVEF) ≤40% measured by transthoracic echocardiography upon hospital discharge and available follow-up LVEF evaluated between 3 months and one year since hospital discharge were selected from a prospective registry of MI patients (n=1323). Results: In total, data from 183 patients (mean age 64.2±11.2, 29% female, mean EF upon discharge 32.6±5.8) were analyzed. In the multivariate linear regression, IL-6 level measured within 24 hours from the hospital admission was positively associated with NT-proBNP, maximal hs-Troponin T a glycemia level and negatively with female gender, total cholesterol and admission systolic blood pressure. During follow-up, LVEF increased by 6.1±9.0% and LVEF recovered to value >50% in 43 (23.5%) patients. In the multivariate analysis, LVEF improvement was predicted by lower IL-6, lower maximal troponin level, female gender, lower heart rate at the time of hospital admission and Killip class I. In the ROC analysis (AUC 0.72, p<0.001), IL-6 ≤ 15.7ng/L had 51% sensitivity and 87% specificity to predict LVEF recovery. Conclusion: The inflammatory response to MI, as assessed by IL-6, is associated with MI size, glucose and lipid metabolism and is lower in women. IL-6 independently predicts change in LVEF among patients with moderate to severe LV dysfunction. This supports previous findings that IL-6 inhibition can increase myocardial salvage after MI and identifies possible patients that may benefit from targeted therapy.